The Philippines on the road to being an emerging economy - Canlas, Dante B. (2015)
In the 1980s, the Philippines was viewed as a failure in terms of its goal to industrialize. But in the past few years of the current century, the country’s economic prospects improved and the country is predicted to be joining the next group of “breakout nations”. The paper looks at the short-run macroeconomic policy reforms and long-term growth-oriented policies since 1986 that have contributed to improved growth performance and bright economic prospects. A responsible budget deficit-reduction program and investments in factors that support long-run growth, such as human capital, have been helpful. Moving forward, stabilization policy has gotten more challenging in an environment of mobile international capital, flexible exchange rates, and “quantitative easing”. In the long run, policies conducive to technological progress are essential.
Keywords: Economic development -- Government policy